2010
DOI: 10.1111/j.1469-8137.2010.03490.x
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype analysis of the genes encoding glutamine synthetase plastic isoforms and their association with nitrogen‐use‐ and yield‐related traits in bread wheat

Abstract: Summary• Glutamine synthetase (GS) plays a key role in the growth, nitrogen (N) use and yield potential of cereal crops. Investigating the haplotype variation of GS genes and its association with agronomic traits may provide useful information for improving wheat N-use efficiency and yield.• We isolated the promoter and coding region sequences of the plastic glutamine synthetase isoform (GS2) genes located on chromosomes 2A, 2B and 2D in bread wheat. By analyzing nucleotide sequence variations of the coding re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 45 publications
3
64
3
Order By: Relevance
“…In contrast, the SNPs we have identified map to 2DL and are not in LD with previously reported Ppd-D1 marker data for these genotypes (Grogan et al 2016). Glutamine synthase 2 genes are located in distal deletion bins on the long arms of group 2 chromosomes and are potential candidates for future investigation, given their important role in previous studies (Li et al 2011).…”
Section: Association Analysiscontrasting
confidence: 46%
“…In contrast, the SNPs we have identified map to 2DL and are not in LD with previously reported Ppd-D1 marker data for these genotypes (Grogan et al 2016). Glutamine synthase 2 genes are located in distal deletion bins on the long arms of group 2 chromosomes and are potential candidates for future investigation, given their important role in previous studies (Li et al 2011).…”
Section: Association Analysiscontrasting
confidence: 46%
“…the expression of TaGS2 encoding plastid-located GS (Li et al, 2011). Overexpression of TaNAC2-5A caused the up-regulation of TaGS2 (representing the summed expression of TaGS2-2A, TaGS2-2B, and TaGS2-2D) in both shoots and roots (Fig.…”
Section: Overexpression Of Tanac2-5a Up-regulates the Expression Of Nmentioning
confidence: 94%
“…These studies clearly demonstrate that efficient root-toshoot transport and remobilization of N are required to support plant growth and achieve high yields. In major cereal crops, the N assimilation genes NITRATE REDUCTASE, GLUTAMINE SYNTHETASE (GS), and GLUTAMATE SYNTHASE are known to colocalize with QTLs affecting grain yield and NUE (Hirel et al, 2001;Obara et al, 2001Obara et al, , 2004Habash et al, 2007;Coque et al, 2008;Zhang et al, 2010;Li et al, 2011;Quraishi et al, 2011). Furthermore, a number of studies have shown that ectopic expression of the genes involved in primary N metabolism and amino acid biosynthesis can increase N uptake and assimilation and/or promote plant growth and yield (McAllister et al, 2012).…”
mentioning
confidence: 99%
“…In addition, TaSus2 could influence the responses of KL and KW to N stress, but it had no effect on the response of per-plant yield (Cui et al 2014a). Glutamine synthetase (GS2) is a key enzyme involved in plant N metabolism that is responsible for the first step of ammonium assimilation and transformation into glutamine; thus, it plays a key roles in the growth, N use and yield potential of cereal crops, including wheat (Gadaleta et al 2011;Li et al 2011). Polyphenol oxidase (PPO) activity is highly correlated with the undesirable browning of wheat-based end products, especially Asian noodles (He et al 2007;Liu et al 2012).…”
Section: Novel Stable Qtls and Qtl Co-segregation With Known Genesmentioning
confidence: 99%
“…GPC, particularly glutenin and gliadin content is controlled by a complex genetic system and is strongly affected by the environment. It is an important factor for pasta-making and baking quality and is strongly correlated with WGC, DT, ABS, and ZEL (Zanetti et al 2001;Nelson et al 2006;Suprayogi et al 2009;Li et al 2011). KH, one of the most important determinants of milling yield, has profound effects on the milling, baking and enduse quality of bread wheat ).…”
Section: Introductionmentioning
confidence: 99%